Situs-Situs Watu Kandang Di Lembah Sungai Samin, Kabupaten Karanganyar, Jawa Tengah - Gunadi Kasnowihardjo (Balai Arkeologi Yogyakarta, 1995)
The Watu Kandang site referred to in this paper is a plot of land containing ancient remains in the form of a solid stone arrangement with a rectangular floor, and is believed by the local community to be an ancestor's grave. In the research area, the arranged stones were found scattered around the Kali Samin stream, and successively from upstream to downstream in Pakem, Karangrejo, Ngasinan, Kedungsari, Bodagan, Gondang, Selestri, Sabrang, and Plosorejo hamlets. The nine sites are located in three different locations.